Automatic curtain / Wan Mohd Nazmin Wan Mahmud and Mohd Nizam Wan Ibrahim - Wan Mahmud, Wan Mohd Nazmin; Wan Ibrahim, Mohd Nizam (2004)
Automatic curtain is one of the products that are needed in a smart house. Although it is simple a work to do but it is still important product. This product is produced not for any other reason but to make people life easier since they had work hard all day. Automatic curtain operates by using LDR and infrared sensors. LDR sensor will function only at the morning and night since the curtain will open when it detects light from the sun and will close at night automatically. Due to the LDR sensor operates in the morning and night, infrared sensor is used to open or closed the curtain anytime